2022
DOI: 10.1002/adfm.202206496
|View full text |Cite
|
Sign up to set email alerts
|

Record‐High Responsivity and High Detectivity Broadband Photodetectors Based on Upconversion/Gold/Prussian‐Blue Nanocomposite

Abstract: The development of high-quality and strongly Au conjugated upconversion nanoparticles (UCNPs) is time-consuming and requires specific chemicals. Therefore, a one-pot hydrothermal method is adopted for novel in situ preparation of UCNP@Au composites using a binary functional ethylenediaminetetraacetic salt, which is employed as a surfactant and reducing agent. The composites are electrostatically conjugated with metal-coordinated Prussian blue (PB) to yield UCNP@Au+PB nanocomposites (NCs), which demonstrate 21-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Engineering-driven photodetectors play an important role in various scientific and industrial applications, including nanomaterials, for example, PbS, ZnO, upconversion nanoparticles, and PQDs. [25][26][27][28][29] Recently, Wu et al [30] and Pan et al [27] reported PQDs/MoS 2 , and PQDs/Gr-based hybrid photodetectors with a responsivity of 7.7 × 10 4 and 1.15 × 10 5 AW -1 , respectively. Bera et al [28] demonstrated the responsivity of ≈10 9 A W -1 with Gr/PQDs/Gr-based hybrid phototransistors with a vertical structure with the shortest channel length.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering-driven photodetectors play an important role in various scientific and industrial applications, including nanomaterials, for example, PbS, ZnO, upconversion nanoparticles, and PQDs. [25][26][27][28][29] Recently, Wu et al [30] and Pan et al [27] reported PQDs/MoS 2 , and PQDs/Gr-based hybrid photodetectors with a responsivity of 7.7 × 10 4 and 1.15 × 10 5 AW -1 , respectively. Bera et al [28] demonstrated the responsivity of ≈10 9 A W -1 with Gr/PQDs/Gr-based hybrid phototransistors with a vertical structure with the shortest channel length.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient NIR-to-UV upconversion also requires precise doping of the lanthanide ions in high-quality crystalline particles. The synthesis can now be routinely achieved by several complementary strategies including co-precipitation, [25] thermal decomposition, [26] hydrothermal synthesis, [27] and sol-gel pro-cessing. [28] In particular, co-precipitation and thermal decomposition methods carried out in organic solvents can give access to the core-multishell nanoparticles with accurate control over shell thickness and particle morphology, [16,29] thus, enjoying common usage by the community.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanides possess unique optical characteristics due to their intra 4f–4f transitions, resulting in color specificity and sharp emission bands. Ln-based NCs demonstrate both Stokes (downshifting, DS) and anti-Stokes (upconversion, UC) emission processes, depending on the sensitizer and activator ions . Ln-based NCs can be excited under UV light (254 or 350 nm) or NIR light (800, 980, and 1550 nm). For example, in the UC process, Er (green and red), Tm (blue), and Ho (green and red) ions serve as activators, with Yb and Nd acting as sensitizers for excitations of wavelengths 980 and 800 nm, respectively .…”
mentioning
confidence: 99%